EFEKTIVITAS KOMUNIKASI APLIKASI TELEGRAM SEBAGAI MEDIA INFORMASI PEGAWAI PT.POS INDONESIA (PERSERO) KOTA PEKANBARU - Nova, Sari Puti; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Telegram application is one of the new media in Indonesia. Telegram is not only effective for communcating, but also effective when used as a online information providers either general information or special information. One of the users who use telegram app is PT.Pos Indonesia Pekanbaru as employees information media. The Theory used in this research is new media theory. The purpose of this research is to investigate how big the effectiveness of Telegram application as an employees information media.This research uses quantitativ research methods, the technique of collecting data in this study is using questionnaire to PT. Pos Indonesia Pekanbaru employees with 82 sample counts that are determined through random sampling techniques the analysis techniques data in this research using descriptive statistical techniques.The results of this research indicate that the level of Telegram Application as Employees Information Media PT.Pos Indonesia Pekanbaru classified as very effective. This has been proven by result of collected data that have been measured by six indicator, each indicator reaches a scale of 3,30 on the receiver or user indicator, scale of 3,33 on the content indicator, scale of 3,42 on the channel indicator,scale 3,40 on the format indicator, scale 3,44 on the source indicator,and scale 3,22 on the timing indicator. The conclusion obtained by using the average formula of all indicator is 3,35 which is included in a very effective scale range. This indicate that Telegram Application is a very effective as a information media to employees PT.Pos Indonesia pekanbaruKeywords: Communication Effectivity, Information, Telegram